Completeness of Medical Record Documents: Exploration of Causes and Solutions - Syukria, Orin Annahriyah; Wardhani, Viera (Fakultas Kedokteran Universitas Brawijaya)
One of the problems identified at X Hospital in the first six months of 2020 was the delay in returning inpatient medical records to the medical records unit. This study was conducted to explore the elements of the incomplete medical records and the factors that contribute to the emergence of delays in returning these documents. This study uses a qualitative method. Exploration was carried out on 21 medical records using a checklist. Besides, data were obtained through interviews involving the head of the relevant unit and a survey of 52 nurses. Data were collected using interview guidelines and nursing work index-revised (NWI-R) instruments. Incompleteness was found mostly in the patient discharge summary form, initial emergency assessment, and initial inpatient medical assessment. Items that have not been completed at most are officer authentication and information on date and time. One of the root causes of this problem is the factor of the nurse. The results of the NWI-R assessment are 3.15 (maximum value 4), which means that the work environment at X Hospital supports nurses in carrying out their duties well. The highest score is 3.31 on the nurse-doctor relationship factor. The lowest score is 2.93 on adequate human resources to ensure quality services.